Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Picture and Picture di Sekolah Dasar - Darmawan, Dodi; Alwi, Nur Azmi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research is motivated by low student learning outcomes. The purpose of this study is to describe the increase in student learning outcomes in integrated thematic learning using the Picture and Picture Type Cooperative Learning Model in Elementary School. This type of research is classroom action research (CAR) which is carried out in two cycles, cycle I consist of 2 meetings, and Cycle II consists of 1 meeting. Each cycle includes planning, implementing, observing, and reflecting. The research subjects were teachers and class III students, totalling 27 people. Data collection techniques in the form of observation, tests, and non-tests. The results showed an increase in: a) lesson plans for the cycle I obtained an average of 82.95% and cycle II 95.45%; b) teacher implementation from the learning aspect, the process in cycle I obtained an average of 84.37% and cycle II 96.87%; c) the implementation of aspects of the first cycle students obtained an average of 85.93% and 96.87% of the second cycle; d) student learning outcomes in the first stage of the cycle obtained an average of 76.37 (C) and cycle II of 88.10 (B). Based on these results, it can be concluded that the Picture and Picture Type Cooperative Learning Model can improve students' integrated thematic learning outcomes in elementary schools.